2013
DOI: 10.1155/2013/601363
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation into the Forced Convective Heat Transfer of Aqueous Fe3O4 Nanofluids under Transition Region

Abstract: The forced convective heat transfer (FCHT) properties of nanofluids, made of Fe 3 O 4 nanomaterials and deionized water, are firstly measured by a self-made forced convective heat transfer apparatus. The nanofluid flows through a horizontal copper tube in the transition region with Reynolds numbers in the range of 2500-5000. Some parameters including Reynolds number, axial distance, and mass concentration are also investigated. The preliminary results are firstly presented that the heat transfer coefficients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Although the heat transfer coefficient of the nanofluid was detected to enhance with the Reynolds number, it decreased with the increase of the concentration and was realized to be lower than the base fluid for all cases. The findings of the Ma et al [43] contradict the other studies in the literature. The possible reason might be the fact that the authors used empirical relation to determine the specific heat value of the nanofluid instead of measurements.…”
Section: Numentioning
confidence: 63%
See 2 more Smart Citations
“…Although the heat transfer coefficient of the nanofluid was detected to enhance with the Reynolds number, it decreased with the increase of the concentration and was realized to be lower than the base fluid for all cases. The findings of the Ma et al [43] contradict the other studies in the literature. The possible reason might be the fact that the authors used empirical relation to determine the specific heat value of the nanofluid instead of measurements.…”
Section: Numentioning
confidence: 63%
“…This was attributed to the chaotic movement of nanoparticles within the fluid. In addition to above studies, a group of researchers found that the ACCEPTED MANUSCRIPT / CLEAN COPY nanoparticles presented in the base liquid increase the thermal conductivity, delay and disturb the thermal boundary layer and accelerate the energy exchange process in the fluid due to the chaotic movement of the nanoparticles [17,8,43], Investigation on convective heat transfer and flow features of nanofluids, 2003). The increase in the thermal conductivity leads to an increase in heat for the MWCNT-water nanofluid at volume concentrations of 0.75% and 1.0%, and reduction in heat transfer coefficient for the MWCNT-water nanofluid at volume concentrations of 0.33%, can be explained by Fig.…”
Section: Friction Factor and Nusselt Number Correlationsmentioning
confidence: 99%
See 1 more Smart Citation